IDO2: A Pathogenic Mediator of Inflammatory Autoimmunity - Lauren M.F. Merlo; Laura Mandik-Nayak (SAGE Publishing, 2016)
Indoleamine 2,3-dioxygenase 2 (IDO2), a homolog of the better-studied tryptophan-catabolizing enzyme IDO1, is an immunomodulatory molecule with potential effects on various diseases including cancer and autoimmunity. Here, we review what is known about the direct connections between IDO2 and immune function, particularly in relationship to autoimmune inflammatory disorders such as rheumatoid arthritis and lupus. Accumulating evidence indicates that IDO2 acts as a pro-inflammatory mediator of autoimmunity, with a functional phenotype distinct from IDO1. IDO2 is expressed in antigen-presenting cells, including B cells and dendritic cells, but affects inflammatory responses in the autoimmune context specifically by acting in B cells to modulate T cell help in multiple model systems. Given that expression of IDO2 can lead to exacerbation of inflammatory responses, IDO2 should be considered a potential therapeutic target for autoimmune disorders.